Концепт свобода в публіцистиці Євгена Сверстюка - Жванія, Людмила Вікторівна; Zhvania, Ludmila (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто світоглядні константи публіциста, письменника-дисидента Євгена Сверстюка, визначальним серед яких постає концепт свобода. Окреслено цілісну картину концепту свобода в публіцистиці Є. Сверстюка, з’ясовано зміст та обґрунтовано значення поняття свобода як філософської категорії; простежено, як здійснюється смислонаповнення концептів свобода, свобода волі у творчості Є. Сверстюка, узагальнено зміст концепту свобода в публіцистичній спадщині письменника. This article shows the specifics of the interpretation of the concept freedom in the works of Eugene Sverstyuk – essayist, dissident writer. Outlined a holistic picture of the concept of freedom in journalism E. Sverstiuk: the author analyzes the content of the concept of freedom as a philosophical category; systematized meanings that are invested in the concept of freedom E. Sverstyuk; summarized the content of the concept of freedom in the journalistic heritage of the writer. The concept of freedom plays a constitutive role in the ideological installation and journalistic creativity Eugene Sverstiuk. The semantic content of this concept includes the following values: freedom as a philosophical-religious category, external freedom as a free social and national existence of the people and freedom of the inner, spiritual. Based on a deep faith, it opens in the soul space of free choice, it becomes a factor of moral perfection personality.
The Concept of Freedom in Journalism Eugene Sverstiuk
Keywords: концепт; свобода; свобода волі; вибір; духовна свобода; concept; freedom; free will; choice; spiritual freedom